Spikes extraction from brain signals - Nicholas Reynaldo, Parmonangan. (2012)
Signal Processing Technique has been vastly explored by signal processing researchers due to its crucial role in terms of research and development for ever-growing biomedical technology field. In 1929, Hans Berger recorded a signal measured from small electrodes attached to scalp named as electroencephalogram (EEG). Since then, this discovery made biomedical signal processing field important has been an interest to analyze and relate the characteristics of the signal to the condition of human body. This area of research is on the rise because of the massive potential applications as well as the technical challenges it poses. Some potential applications are very novel and could bring major changes in human lives, such as disease detection, EEG-based games, and human mental state detection.